Integration of Gamification in the Practice of Social Science Learning Pedagogy in Elementary Schools - Mahpudin Mahpudin; Al Thof Dzafif Nuryana Firdaus; Budi Febriyanto (AL-ISHLAH: Jurnal Pendidikan, 2026)
Low student engagement in Natural and Social Sciences (IPAS) learning remains a persistent challenge in Indonesian elementary education, particularly in contexts where teacher-centered approaches dominate. Gamification has emerged as a promising pedagogical strategy to enhance motivation and participation; however, qualitative insights into its classroom implementation remain limited. This study aims to explore how gamification is applied in primary IPAS learning and how it influences student engagement and motivation.This research employed a qualitative case study design conducted at an elementary school in Majalengka, Indonesia. Data were collected over one week through classroom observations, semi-structured interviews with two teachers and eleven Grade 5 students, and documentation analysis of lesson plans and learning media. Data were analyzed using the interactive model of data reduction, display, and conclusion drawing.The findings indicate that gamification—implemented through digital platforms such as Wordwall and Quizizz, as well as paper-based adaptations—significantly enhanced students’ behavioral, cognitive, affective, and social engagement. Students demonstrated increased participation, enthusiasm, collaboration, and persistence in completing learning tasks. Teachers also reported a more dynamic and interactive classroom environment. However, challenges were identified, including limited instructional time, varying levels of digital literacy, and technical constraints.These results suggest that gamification can serve as an effective and adaptable pedagogical approach to foster student engagement in elementary IPAS learning. Its successful implementation depends not only on technology but also on teachers’ pedagogical design and contextual adaptation, highlighting the need for sustained professional development and infrastructure support.